الصورة في الحجاج الإعلامي خصائصها ووجوه الحجاج فيها The image of the argument in media: its characteristics and the varieties of argument - Abu daher, Mostafa elsayed; Ali, Asem Shehadeh Saleh (2020)
ملخص البحث تنطلق فرضية هذا البحث من أن الخطاب الحجاجي هو خطاب تواصلي وعمل لغوي حجاجي تفاعلي، ومن ثمَّ فللصورة دور حجاجيّ، ولانتقائها حركة حجاجية تأثيريَّة في المتلقي، فبدأ البحث ببيان الخصائص الحجاجيَّة للصورة، فالدراسة التَّداوليَّة للصورة تختلف عن الدراسات السابقة، فالصورة ليست على الإطلاق رائعة أو فاترة أو معبرة، بل يحدد جودة الصورة سياقها الذي اُستخدمت فيه، السياق بكل مشتملاته الزمانيَّة والمكانيَّة والمتحدث والمتلقي والظرف التخاطبيّ، فضلاً عن بيان أثرها في الخطاب الحجاجي لا سيما في الإعلام المرئيّ، فالصورة لا تنجح في دورها تبعاً لجمالها الشكليّ أو الاستعاريّ، بل من ملاءمتها للسياق التَّداوليّ في المقام الخطابيّ بمكوناته، ثم انتقل البحث إلى بيان أنواع الصور وتقسيماتها، ومن ثم بيان الحركة الحجاجية للصورة في برنامج الاتجاه المعاكس. الكلمات المفتاحيَّة: الصورة – الخطاب – الحجاج – الإعلام المرئيّ – المجاز – التشبيه – الاستعارة – الكناية. ABSTRACT: The hypothesis of this research stems from the fact that the argumentative discourse is a communicative discourse and an interactive argumentative linguistic work, then the image has an argumentative role, and its selection is an argumentative movement in the recipient. Lukewarm or expressive. Rather, the quality of the image determines the context in which it was used. The context in all its temporal and spatial implications, the speaker, the receiver, and the communicative circumstance, as well as indicating its impact on the argumentative discourse, in the visual media. The image does not succeed in its role due to its formal or allegorical beauty, but rather from its suitability to the deliberative context in the discursive place with its components. The research moved to an explanation of the types and divisions of the images, and then the pilgrimage movement of the image in the program of the opposite direction. Keywords: image - discourse - pilgrims - visual media - metaphor - simile - metaphor - metonymy.